Ethics briefing - Norcliffe-Brown, Dominic (Journal of medical ethics, 2021)
On 8 October 2020, the British Medical Association published the results of its survey of BMA members on physician-assisted dying. With 28 986 respondents, this was one of the largest surveys of medical opinion on this topic ever carried out. This represents 19.35% of those who received an invitation to participate and the respondents were broadly representative of the BMA’s overall membership (general practitioners were slightly over-represented and medical students and junior doctors were slightly under-represented).The BMA was clear throughout this process that the results of the survey would not determine its policy. Its current policy of opposition to all forms of physician-assisted dying would remain unless and until the Representative Body, which makes BMA policy, decided otherwise. The survey results would, however, inform a future debate on policy, currently scheduled to take place in June 2021.When asked what the BMA’s position should be on whether there should be a change in the law to allow doctors to prescribe drugs for an eligible patient to self-administer to end their own life, 40% said the BMA should be supportive, 33% opposed, 21% thought the BMA should be neutral and 6% were undecided. In relation to their own personal views, 50% were supportive, 39% opposed and 11% undecided. When asked whether they would be willing to participate in some way in the process, if it were to be legalised, 36% said yes, 45% said no and 19% were undecided.The same three questions were asked about a change in the law to allow doctors to administer drugs to end the life of an eligible patient. In response, 40% thought the BMA should oppose such a change, 30% thought the BMA should be supportive and 23% thought the BMA should be neutral; 7% of members responding were undecided on this question. In …